Physicochemical characterization of native and modified sodium caseinate- Vitamin A complexes. (April 2018) - Gupta, Chitra; Arora, Sumit; Syama, M.A.; Sharma, Apurva
Abstract: Native and modified sodium caseinate- Vitamin A complexes {Sodium caseinate- Vit A complex by stirring (NaCas-VA ST), succinylated sodium caseinate- Vit A complex by stirring (SNaCas-VA ST), reassembled sodium caseinate- Vit A complex (RNaCas-VA) and reassembled succinylated sodium caseinate- Vit A complex (RSNaCas-VA)} were prepared and characterized for their physicochemical characteristics e.g. particle size, zeta potential, turbidity analysis and tryptophan intensities which confirmed structural modification of both native (NaCas-VA ST) and modified (SNaCas-VA ST, RNaCas-VA and RSNaCas- VA) proteins upon complex formation with vitamin A. Binding of vitamin A to milk protein reduced the turbidity caused by vitamin A, however, the particle size and zeta potential of milk protein increased after complexation. Microstructure details of NaCas (spray dried) showed uniform spherical structure, however, other milk proteins and milk protein- Vit A complexes (freeze dried) showed broken glass and flaky structures. Tiny particles were observed on the surface of reassembled protein and reassembled protein- Vit A complexes. Binding of vitamin A to milk protein did not have an influence on the electrophoretic mobility and elution profile (RP-HPLC). Graphical abstract: Unlabelled Image Highlights: Native and succinylated sodium caseinate- Vitamin A complexes were prepared. Binding of vitamin A to milk protein increased the particle size and zeta potential. Tryptophan intensities confirm the structural modification in milk protein. Complex formation have no influence on electrophoretic mobility and elution profile.